Does an Increase in Iron Content Affect the Shrinkage Porosity of Secondary Al-Si Alloys? - Piątkowski, J.; Gródek, K.; Fusiarz, J. (Archives of Foundry Engineering, 2026)
This article attempts to answer the question of which theory of porosity formation in Al-Si alloy castings is correct? The one that suggests shrinkage porosity results from the presence of plate-like β-Al5FeSi phases in the alloy, or the one that porosity is caused by thin, double-layer oxide films? The study was conducted on an AlSi7Mg alloy with an increased content of secondary materials (from 45% to 65%), gravity cast at low pressure (up to 0.15 MPa). It was shown that the main factor that determines the causes of shrinkage porosity in aluminium alloys is the method of delivering the liquid metal to the mould cavity. The microstructure examination results of the gravity-cast AlSi7Mg alloy showed that, with increasing iron content, the quantitative fraction of the β-Al₅FeSi phase increases, and their length grows from approximately 40 μm (at 0.4 wt.% Fe) to about 700 μm (at 0.8 wt.% Fe). Under such conditions, the dominant cause of shrinkage porosity in castings is the b-Fe phase, whose unfavorable morphology blocks the interdendritic alloy flow channels. This results in decreased permeability between dendrites α(Al), and consequently increased casting porosity. In pressure castings, the proportion of β-Fe phases is negligible (length up to approximately 30 μm). Numerous oxides were found in close proximity to shrinkage pores. After solidification of the AlSi7Mg alloy, these air "gaps" constitute pores that are not associated with β-Fe phases. Therefore, it can be concluded that in pressure castings, thin oxide films ("bifilms") are a more significant cause of shrinkage porosity than the β-Fe phases.